ผลการใช้โปรแกรมการป้องกันการหกล้มของผู้สูงอายุต่อประสิทธิผลของทีมการพยาบาลและพฤติกรรมการป้องกันการหกล้มของผู้สูงอายุในชุมชน - ฐิติมญชุ์ ปัญญานะ (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
The purpose of this research were to 1) compare fall prevention behaviors of community-dwelling elders before and after using fall prevention program 2) compare the effectiveness of nursing team before and after using fall prevention program. The research subject composed of 1) 12 professional nurses in Chiangklang community hospital and primary care units in Chiangklang district. 2) 34 community-dwelling elders who were fall risk group, 60-75 years old. The research instruments were fall prevention training project, fall prevention practice program, fall prevention manual for nurses and, fall prevention manual for community-dwelling elders and their familys, effectiveness of nursing team questionnaire and prevention behaviors interview form, tested for content validity by 5 experts, the validity were 1, .77 respectively, the Cronbach’s alpha coefficients were .89, .77 respectively. Statistical techniques utilized in data analysis were frequency, percentage, mean and t-test. Major finding of this study were as follows: 1. Fall prevention behaviors of community-dwelling elders after using fall prevention program were higher than before using fall prevention program significantly. 2. The effectiveness nursing team to prevent falls after using fall prevention program was significantly higher than before using fall prevention program significantly.